Pengenalan Cabang Olahraga Pentanque Kepada Peserta Didik di Sekolah Dasar Uptd Satdik SDN Tamansari 01 - Septanania Septanania; Ahmad sulaiman (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
. Petanque is a relatively new sport at the moment. This pétanque sport includes games where the props are an iron ball (BOSI) and a wooden ball (BOKA). In this game the target is to throw the iron ball so that it is closest to the wooden ball. This research was conducted to find out how developed the sport of pétanque is among school students. The method used in this research is by conducting outreach to students in grades 4 and 5 of elementary school. This article was created to provide insight and knowledge about the sport of pétanque to elementary school students. This is done so that it can produce outstanding pétanque athletes.